MIMOSINE - A NOVEL SUBSTANCE AND EVALUATE THE LIPID PEROXIDATION - K G, DHANYA; M, THANGAVEL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The mimosine is a novel substance extracted and purified from Mimosa pudica. The present study is to evaluate lipid peroxidation (LPO). Methods: The sox halation is used to differentiate extracts. Mimosine is purified by gas chromatography–mass spectrometry (GC–MS) and liquid chromatography–mass spectrometry (LC–MS). The present study was conducted to evaluate the hepatoprotective activity of ethanol extract of M. pudica against alcohol-induced albino rats. This was evident from significant of M. pudica on LPO and antioxidants liver of rats. Results: By GC–MS and LC–MS, the mimosine is purified and it shows the highest peak. The phytochemical analysis of M. pudica and the activity of the enzyme antioxidants such as superoxide dismutase is 176.83 g and peroxidase is 0.989 g, were found to be present in the plant extract of M. pudica. In rat treated with toxic dose of alcohol, a significant increase in serum and liver were observed. Simultaneous oral administration of the aqueous extract of M. pudica reduced the lactate dehydrogenase (LDH) activity to a significant extent compared to control. LDH, a cytosolic liver marker enzyme, is a regulator of many biochemical reactions in the body tissues and the fluid. Conclusion: The result obtained in our work, existence of bioactive substance proves that it is mainly used as a traditional medicine. The phytochemical analysis indicated the presence of alkaloids, steroids, terpenoids, tannin, phenolic, saponins, proteins, and amino acids. The liver showed that the induction of alcohol causes hepatic necrosis and injury, but it is cured by M. pudica.